Modelling and optimisation of a mechanism-based metamaterial for a wrist flexion-extension assistive device - Raghavendra Kulkarni, Suhas (2021)
In this paper we present a methodology for optimising the design of a metamaterial structure with one degree of freedom that is able to simultaneously bend and stretch. The structure is intended for assisting flexion-extension of the wrist joint. The metamaterial is comprised of serially connected, in- dividually designed cells. The design parameters can be chosen to optimally fit a desired planar curve such as the curvature of the skin on a plane normal to the flexion/extension axis of the wrist joint. A tool for the optimised design is described and the experimental validation of the output is conducted, to show the ability of the mechanism to conform to a 2D curve, also exhibiting a change in length, which is desirable for reducing sliding and shear on the skin. The design tool allows the generation of metamaterials optimised for a multitude of other applications where actuated mechanisms must be worn by a user for rehabilitation or assistance purposes.